Model Pembelajaran Double Loop Problem Solving (DLPS) dalam Pembelajaran Fisika pada Materi Gerak Melingkar Beraturan - Muhammad Yoggi Prastya Batulieu (Edukhasi: Jurnal Inovasi Pendidikan, 2023)
The purpose of writing this article is 1) To explain the DLPS (Double Loop Problem Solving) learning model; 2) To explain the steps of the DLPS (Double Loop Problem Solving) learning model; 3) To explain the advantages and disadvantages of the DLPS (Double Loop Problem Solving) learning model; and 4) To compile the syntax for learning Physics with the DLPS (Double Loop Problem Solving) model in the subject of Circular Motion. The method used in writing this article is the library method. The data analysis techniques in this article are summarizing, presenting theory, and providing conclusions. Based on the discussion that has been done, it can be concluded that 1) DLPS (Dooble-Loop Problem Solving) is a modification of learning problem solving with an emphasis on finding the main causes of the emergence of a given problem; 2) The steps of DLPS (Dooble-Loop Problem Solving) are Identifying the problem, Detecting direct causes, and rapidly applying temporary solutions, Evaluating the success of the temporary solutions, then Deciding if root cause analysis is needed, If so, detecting higher level causes and Designing root causes solutions; 3) The advantages of the DLPS (Double Loop Problem Solving) learning model are practising students to design an invention, think critically, solve problems faced realistically, identify and carry out investigations, interpret and evaluate the results of observations and stimulate the development of students' thinking progress. Disadvantages of the DLPS (Double Loop Problem Solving) learning model are require a longer time allocation, difficulty in evaluating the problem-solving process constantly, difficulty finding the right problem or in accordance with the level of development and abilities of students; and 4) The DLPS (Dooble-Loop Problem Solving) syntax is identification, causal detection, tentative solution, solution consideration, causal analysis and selected solution plan.